Perception and Use of Radio in the Information Age - A Survey of Accra Academy and Accra Girls' High Schools in Ghana - Addo, Joseph Tuffour (UniMAC-GIJ, 2015)
In the face of rapid increase in new media technology, previous scholarly research has attached much interest to the intersections and dynamics between traditional media and new forms of communication. Still, radio dominates as a major mass medium in Ghana and Africa. The study examined the radio listening habits of adolescents in an era of digital technology. It surveyed 300 high school students in Ghana specifically with regards to gratifications sought; gratifications obtained from listening to radio and the mode of accessing radio. The research further investigated whether or not radio in Ghana is serving the needs of adolescents as well as the extent to which other media outlets in the information age are having displacement effects on traditional radio, within the framework of the Uses and Gratifications and the Niche theories. It panned out from the investigation that majority of the students listen to radio in order to be entertained and informed on current happenings and healthy lifestyle. The traditional radio set turned out to be the single most preferred device for listening to radio as a result of its comparative advantage such as affordability and accessibility to non working students. The results of the investigation further indicated that, adolescent girls in Ghanaian High Schools prefer accessing radio with Inobile phones thari their male counterparts who relied more on advanced devices such as MP3. In order to get the most of entertaimnent, celebrity interviews, sports and current affairs respectively. It elnerged from the research that, although adolescents still listen to radio, a significant number of students no longer fancy radio in Ghana due to interjections of favourite music by D1s; presence of invectives and too many ads on alcohol and condoms.
MA Journalism